Inhibition of Antimicrobial-Resistant Escherichia coli Using a Broad Host Range Phage Cocktail Targeting Various Bacterial Phylogenetic Groups - Kim, Jinshil; Park, Haejoon; Ryu, Sangryeol; Jeon, Byeonghwa (Frontiers in Microbiology, 2021)
Antimicrobial-resistant (AMR) commensal Escherichia coli is a major reservoir that disseminates antibiotic resistance to humans through the consumption of contaminated foods, such as retail poultry products. This study aimed to control AMR E. coli on retail chicken using a broad host range phage cocktail. Five phages (JEP1, 4, 6, 7, and 8) were isolated and used to construct a phage cocktail after testing infectivity on 67 AMR E. coli strains isolated from retail chicken. Transmission electron microscopic analysis revealed that the five phages belong to the Myoviridae family. The phage genomes had various sizes ranging from 39 Kb to 170 Kb and did not possess any genes associated with antibiotic resistance and virulence. Interestingly, each phage exhibited different levels of infection against AMR E. coli strains depending on the bacterial phylogenetic group. A phage cocktail was constructed using phages capable of infecting AMR E. coli in phylogenetic groups A and B1, the major phylogenetic groups of E. coli isolates from retail chicken, and inhibited 91% (61/67) of AMR E. coli strains used in this study. Furthermore, the phage cocktail was effective in inhibiting E. coli on chicken at refrigeration temperatures. The treatment of artificially-contaminated raw chicken skin with the phage cocktail rapidly reduced the viable counts of AMR E. coli by approximately 3 log units within 3 h, and the reduction was maintained throughout the experiment without developing resistance to phage infection. These results suggest that phages can be used as a biocontrol agent to inhibit AMR commensal E. coli on raw chicken.